Pandemic Impact on Financial Strength of Cities of East Poland - Jacek SIERAK (Communications of International Proceedings, 2021)
The main research problem of the paper is the analysis of the impact of the covid pandemic on the financial situation of cities, carried out on the basis of an assessment of the situation of units located in East Poland. The pandemic has been met with crisis-response and adaptive measures not only from Polish government but also local governments. In this peculiar time cities have faced an arduous situation due to new challenges and a large spike in demand for services falling under the umbrella of a municipality’s own tasks (as opposed to delegated from the central government) in the area of access to health-care, reorganization of employment and education, as well as the assurance of public safety. The surge in these tasks has consequently increased the demand for whatever was necessary in order to execute them. At the same time, some local governments have experienced a dwindling of own revenues.The purpose of this article is to demonstrate the impact of the Covid-19 pandemic on the financial strength of cities in East Poland. To this end the vulnerability of select important sources of their budget revenue to the crisis situation will be studied, and relationships between current income and current expenditure, as well as changes to indebtedness figures will be demonstrated
Keywords: Territorial Self-Government Finances; Covid 19; Local Development.